2011
DOI: 10.1007/s11249-011-9891-6
|View full text |Cite
|
Sign up to set email alerts
|

Slurry Erosion Behaviour of Detonation Gun Spray Al2O3 and Al2O3–13TiO2-Coated CF8M Steel Under Hydro Accelerated Conditions

Abstract: Slurry erosion performance of detonation gun (D-gun) spray ceramic coatings (Al 2 O 3 and Al 2 O 3 -13TiO 2 ) on CF8M steel has been investigated. Slurry collected from an actual hydro power plant was used as the abrasive media in a high speed erosion test rig. Attempt has been made to study the effect of concentration (ppm), average particle size and rotational speed on the slurry erosion behaviour of these ceramic-coated steels under different experimental conditions. The analysis of eroded samples was done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 23 publications
(19 reference statements)
2
14
0
Order By: Relevance
“…Taguchi's L4 methodology was used to optimize the total number of experimental runs as Taguchi method in comparison with other methods leads to a reduction of the experiment runs in order to study the different combinations of factors and their levels resulting in quicker testing to achieve required results. 20 Table 5 shows the experimental plan along with various values of operational parameters during each experiment. The results were recorded as specific mass loss (SML), which is determined by calculating the mass loss of each specimen per unit peripheral area for each hour of testing.…”
Section: Testing Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taguchi's L4 methodology was used to optimize the total number of experimental runs as Taguchi method in comparison with other methods leads to a reduction of the experiment runs in order to study the different combinations of factors and their levels resulting in quicker testing to achieve required results. 20 Table 5 shows the experimental plan along with various values of operational parameters during each experiment. The results were recorded as specific mass loss (SML), which is determined by calculating the mass loss of each specimen per unit peripheral area for each hour of testing.…”
Section: Testing Conditionsmentioning
confidence: 99%
“…Various attempts have been made in the past in the field of developing a correlation between the mass loss during the slurry erosion and influential parameters. 17,18 Many researchers [18][19][20][21] have presented empirical correlations for determining slurry erosion rate of different surfaces under the influence of various slurry related factors. Gupta et al 18 proposed the following relation to express the effect of significant parameters on the erosion rate of exposed materials…”
Section: Introductionmentioning
confidence: 99%
“…7 Detonation coatings are designed for applying hard materials, especially carbides, on surfaces subject to aggressive wear. 810…”
Section: Introductionmentioning
confidence: 99%
“…They have properties like high hardness because of their pure ceramic nature. So, they were unconcerned to may erosion and corrosion environments [5] [6]. KVS Rao et al have studied the slurry erosion behaviour of plasma sprayed TiO 2 coatings on 410 steel substrate by varying the slurry rotational speed and reported that TiO 2 coated substrates possess more erosion resistance as compared to uncoated substrates [7].…”
Section: Introductionmentioning
confidence: 99%